2001
DOI: 10.1111/j.1741-3737.2001.00247.x
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Satisfaction and Physical Pleasure in Sexual Unions: Time Horizon, Sexual Behavior, and Sexual Exclusivity

Abstract: Health and Social Life Survey to examine emotional satisfaction and physical pleasure from sex in intimate unions for adults in the U.S. Using perspectives from evolutionary biology and rational choice theory, we examine the effects of the following factors on emotional satisfaction and physical pleasure: time horizon expected for the relationship, sexual behavior within the relationship, and sexual exclusivity. We find a significant effect of measures for all 3 of these dimensions on emotional satisfaction wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
108
2
12

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 171 publications
(126 citation statements)
references
References 26 publications
4
108
2
12
Order By: Relevance
“…Mutual affection may enhance sex whether or not it is accompanied by a long-term commitment. Waite and Joyner (2001b) find that men and women report greater emotional satisfaction in sexually exclusive relationships that they expect to last a long time. Other scholars have found that relationship satisfaction influences sexual satisfaction and vice versa (Christopher and Sprecher 2000;Parish et al 2007).…”
Section: Conceptions Of the Sources Of Sexual Satisfactionmentioning
confidence: 88%
“…Mutual affection may enhance sex whether or not it is accompanied by a long-term commitment. Waite and Joyner (2001b) find that men and women report greater emotional satisfaction in sexually exclusive relationships that they expect to last a long time. Other scholars have found that relationship satisfaction influences sexual satisfaction and vice versa (Christopher and Sprecher 2000;Parish et al 2007).…”
Section: Conceptions Of the Sources Of Sexual Satisfactionmentioning
confidence: 88%
“…Women, in particular, appear to regard sexuality from a relational orientation in which sexuality is viewed as one aspect of an intimate relationship (Waite & Joyner, 2001). Therefore, an encompassing theory of female sexuality needs to consider the larger relationship context and it needs to address all women, not merely heterosexual women.…”
Section: Introductionmentioning
confidence: 99%
“…Women with dyspareunia have selfreported more negative feelings surrounding sexual activity (Nunns & Mandal, 1997;Wouda et al, 1998), less sexual pleasure (Reissing, Binik, Khalifé, Cohen, & Amsel, 2003), more feelings of depression about sexuality (Gates & Galask, 2001), and negative sexual attitudes (Meana et al, 1997). Furthermore, one's sexual schema can be influenced by a number of sexual experiences, including age of sexual intercourse debut (Haavio-Mannila & Kontula, 1997;Sprecher, Barbee, & Schwartz, 1995), early non-intercourse sexual experience (Davis & Lay-Yee, 1999), number of sexual partners, exclusivity within a sexual relationship (Waite & Joyner, 2001), and importance of sex (Byers, 2005). Attitudes about gender-typical sexual behavior may also impact future sexual activity (Milhausen & Herold, 1999).…”
Section: Introductionmentioning
confidence: 99%